Natal tooth with Riga Fede disease: A case report - Jamani, Nurjasmine Aida; Ardini, Yunita Dewi; Harun, Nor Asilah (2017)
Natal tooth and neonatal tooth is a rare occurrence but can have a significant impact on lactation. A 45-day-old baby girl was referred for problem with breastfeeding. Her mother complained of painful nipple during nursing for the past two weeks. Physical examination of the mother's breast and nipple revealed normal findings. Examination of the baby's oral cavity revealed a natal tooth over the mandibular anterior region, small in size, whitish opaque in colour and exhibiting grade 1 mobility. There was a whitish ulcer over the ventral aspect of the tongue. A diagnosis of natal tooth in association with Riga Fede disease was made. The baby underwent tooth extraction under topical anaesthesia. Subsequently, breastfeeding was able to be continued without any problem. Hence, extraction of natal tooth should be individualized and properly assessed.